Formação graduada nos cursos brasileiros de terapia ocupacional para o ensino voltado aos contextos territoriais e comunitários - Carrasco-Bassi, Bianca Gonçalves de (2024)
Since the 1990s, theoretical/practical/methodological strategies linked to territorial and community contexts have emerged in the teaching of occupational therapy in Brazil. Focusing on the teaching-learning process, these contexts are living spaces involved in the production of knowledge and practices, composed of a confluence of knowledge and actions that reflect the plurality of trajectories of Brazilian occupational therapy, in health, education, arts, in culture and society. Thus, this research aimed to present a current panorama of teaching focused on territorial and community contexts in graduate training in occupational therapy. As a methodological resource, we used documentary research based on national curricular guidelines, pedagogical projects of participating courses and teaching plans. In addition to virtual questionnaires and conversation circles with teachers. The data was presented, organized and analysed using thematic analysis. The results demonstrate that territory and community are structuring concepts of this teaching, they are incorporated into the documents guiding training in the country, but they dialogue with the concepts of social participation, ways of life, territoriality, urban mobility, interculturality, structural racism, popular education, rights humans, among others. Training in these contexts incorporates teaching and professional practice as elements for transforming social, cultural and health realities. In this conjunction, this teaching incorporates practical rationality in graduate training, encouraging critical and ethical reflection within the territories, being built in the dialogical relationship between students, teachers, teams, services, professionals and communities. It is organized by curricular components that present content in a transversal way, but five of them address the topic in a specific way. Most of the training actions are linked to the practical components of the curricula, which present professional practices, supervised internships and extension actions in the territories. We concluded that the research brought elements about/for this teaching in the Brazilian context that contribute to the training of occupational therapists committed to social transformation and territorial actions. In this way, in contrast to technical rationality, this training requires practical rationality, relying on situated and reflective learning, being fundamental for the subareas that support it, but also for all practices of the profession, even if the professional can later specialize- and for actions in other specific contexts.